Nursing Staff Shortage: How About Retention Rate? - Marzieh Adel-Mehraban; Azam Moladoost (Zanjan University of Medical Sciences and Health Services, 2019)
Background: The main task of health managers is to select and hire efficient personnel and to retain them. Objectives: It is therefore necessary for managers to be aware of the status of their staffs. Due to the lack of access to information about nurseschr('39') retention rate in Iran, the researchers intended to design this study and perform it in public and private hospitals in Isfahan. Methods: This is a retrospective study based on information available in the past five years. In this study, in coordination with the competent authorities by completing a pre-prepared form, the necessary information was collected to measure the retention rate of nurses in public and private hospitals and the retention rate of nurses were calculated and reported. Results: The study showed that during the five years in 15 hospitals, in Isfahan form 2013-2017 totally 902 nurses had left their work in five years (89% women and 11% men), the majority of nurses were female (89%), the highest leaving was in 2013 (229 individuals) and the lowest leaving was in 2017 (125 individuals). Most of the departures in public hospitals were related to Completion of national academic obligations (58%), retirement (23.4%), sickness absenteeism and maternity leave (20.2%), resignation (16.4%). and extrusion (3%). Most of the departures in private hospitals were due to resignation (31.2%), sickness absenteeism and maternity leave (15.4%), retirement (8.2%), and extrusion (0.4%). Also, the maximum retention in public centers was (95.8%) and the minimum was in private hospitals (76%). Nurseschr('39') retention rate was increased from 2013 to 2017. Conclusion: Overall, the results of this study showed the large number of resignations in non-governmental centers indicate that nursing managers in these centers need to pay more attention to increasing job satisfaction and safety of nurses.